(untitled) (Web of Teachers: Inderscience Research, 2026)
Emotional regulation is a set of conscious and unconscious processes that aim to manage a person’s emotional states, maintain internal balance, and adapt to changing environmental conditions. At the student age, there is a special dynamic of emotional processes due to the high level of academic workload, social adaptation, the need to master new roles and a high degree of uncertainty about the future. All these factors predispose to an increased level of anxiety, which, in turn, actualizes the problem of effective emotional regulation in this age period.